Leaching and Residual Kinetics of Chloramphenicol Incorporated Medicated Feed Treated to Juvenile Black Tiger Shrimp Penaeus monodon - Selvin, Joseph; A.P., Lipton (Fishery Technology, 2025)
The leaching rate of chloramphenicol (CAP) incorporated medicated feed after immersion in water was high during the first 10 min. About 30% loss of CAP from the medicated feed was observed after 2 h of immersion. The leaching rate was not uniform in the period of 10 h experiments. Juvenile black tiger shrimp Penaeus monodon fed for 7 days with recommended dose (50-100 mg/kg shrimp) of CAP were examined for residual accumulation and depletion. A higher residue of 7.10 mg/g shrimp tissue was found after 1 day of postdosing. This was estimated as 2.15% of the total CAP intake in the7 days of experimental period. By the 20th day following cessation of medicated feed treatment the CAP concentration was found below detectable limit.